Indacaterol : the first once-daily long-acting Beta2 Agonist for COPD - Trifilieff, Alexandre (Milestones in Drug Therapy, 2014)
Chronic obstructive pulmonary disease (COPD) is a multi-component condition that results in increasingly limited airflow, usually associated with an abnormal inflammatory response of the lung. It constitutes a major public health burden worldwide, while only very few effective therapies are available. This book provides a comprehensive overview of the development of Onbrez Breezhaler, a newly approved once-daily inhaled β2 agonist for the treatment of COPD. It reviews the current pharmacotherapy for COPD and discusses topics such as the chemical design and the pre-clinical pharmacology of the molecule, the early clinical development, the INHANCE study (which provides a successful example of the use of an adaptive design in the confirmatory setting) and the Phase III clinical efficacy study, as well as the history and performance of the Breezhaler device. Finally, a list of emerging targets is included that could well offer future treatment options for COPD.